Self-reported food safety knowledge and behaviour among Home and Consumer Studies students. (September 2016) - Lange, Marie; Göranzon, Helen; Marklinder, Ingela
Abstract: Home and Consumer Studies (HCS) should be a suitable place for food safety education as it includes plenty of practical cooking and is compulsory for all students in the Swedish school system. A study among HCS teachers however reveals shortcomings in food safety teaching. A survey regarding food safety knowledge and behaviour among HCS students in school Year 9 was performed at different schools with a new system to collect questionnaire data. A Student Response System was used at the participating schools. The students were to answer the questions by using a small handheld wireless control, a clicker, in the response program Turning Point 2008. The questionnaire included a total of 26 questions and all questions were shown at PowerPoint slides and read out loud to the students. Some trivial questions were asked at the beginning to ensure the method. A total of 529 students from 18 different schools in different parts of Sweden participated in the survey conducted between September 2013 and January 2014. The survey results were evaluated and analysed using SPSS by performing cross-tabulation and chi-square tests. This study reveals that the students' self-reported food safety knowledge and behaviour are inadequate. Important risk areas need to be highlighted in HCS teaching. Boys reported to be significantly more at risk in terms of food safety regarding the handling of risk foods, reheating and cleaning. Especially for boys who reported seldom cook at home HCS would be extra valuable. This study also indicates the importance of reflection in relation to the hygiene routines which are common in the HCS context. The outcome of this study is that students might leave school without even basic food safety knowledge. Highlights: Boys were reported to be more at risk in terms of food safety. Different risk areas need highlighting in teaching. Food safety practices need to be reflected upon. Students who cook regularly reported a safer practice. A Student Response System was used for data collection.